2016
DOI: 10.1016/j.resp.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent plasticity in the isolated embryonic avian brainstem following manipulations of rhythmic spontaneous neural activity

Abstract: When rhythmic spontaneous neural activity (rSNA) first appears in the embryonic chick brainstem and cranial nerve motor axons it is principally driven by nicotinic neurotransmission (NT). At this early age, the nicotinic acetylcholine receptor (nAChR) agonist nicotine is known to critically disrupt rSNA at low concentrations (0.1–0.5 µM), which are levels that mimic the blood plasma levels of a fetus following maternal cigarette smoking. Thus, we quantified the effect of persistent exposure to exogenous nicoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…However, jump performance in frogs is reduced after hibernation (Renaud & Stevens, ), implying that a cold body temperature does not mean that all motor systems will necessarily retain the capacity for normal function throughout the winter. In addition, recent work in the respiratory control system of birds and rodents shows that rhythm generating networks and motoneurons exhibit compensation in response to activity challenges (Braegelmann, Streeter, Fields, & Baker, ; Mahamed, Strey, Mitchell, & Baker‐Herman, ; Vincen‐Brown, Revill, & Pilarski, ). These data suggested that the hibernation environment may trigger homeostatic forms of plasticity that are integrated to help frogs breathe adequately after inactivity.…”
Section: Evidence For Compensatory Forms Of Plasticity In the Respiramentioning
confidence: 99%
“…However, jump performance in frogs is reduced after hibernation (Renaud & Stevens, ), implying that a cold body temperature does not mean that all motor systems will necessarily retain the capacity for normal function throughout the winter. In addition, recent work in the respiratory control system of birds and rodents shows that rhythm generating networks and motoneurons exhibit compensation in response to activity challenges (Braegelmann, Streeter, Fields, & Baker, ; Mahamed, Strey, Mitchell, & Baker‐Herman, ; Vincen‐Brown, Revill, & Pilarski, ). These data suggested that the hibernation environment may trigger homeostatic forms of plasticity that are integrated to help frogs breathe adequately after inactivity.…”
Section: Evidence For Compensatory Forms Of Plasticity In the Respiramentioning
confidence: 99%
“…On the other hand, feedback mechanisms appear to protect the drive to breath by stabilizing motor output in response to environmental perturbations. Along these lines, respiratory motor inactivity in different vertebrate species triggers plasticity that can compensate for this disturbance to restore respiratory activity (Streeter and Baker-Herman, 2014;Brown et al, 2016;Santin, 2019). To date, most mechanistic work has focused on excitatory synapses of motoneurons as targets of such plasticity; however, alterations in fast synaptic inhibition are often triggered by changes in neuronal activity in a variety of different neural systems (Benevento et al, 1995;Hendry et al, 1994;Hendry & Jones, 1986, 1988Rutherford et al, 1997;Hartman et al, 2006;Kilman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%